A guide to new religious movements - Enroth, Ronald (InterVarsity Press, 2005)
What is a new religious movement? / Ronald Enroth -- Jehovah's Witnesses / Ron Rhodes -- Yoga and Hinduism / Vishal Mangalwadi with Ronald Enroth -- Unification Church / James Beverly -- Latter-day Saints / Robert M. Bowman, Jr. -- Astral religion and the New Age / Charles Strohmer -- The Dalai Lama and Tibetan Buddhism / James C. Stephens -- Neopaganism / John Peck -- The Baha'i World Faith / Francis J. Beckwith -- The Nation of Islam / Craig S. Keener and Glenn Usry -- Evaluating new religious movements / LaVonne Neff